Organic amendments conditions on the control of Fusarium crown and root rot of asparagus caused by three Fusarium spp. - Borrego-Benjumea, Ana I.; Melero-Vara, José M.; Basallote-Ureba, María J. (Spanish Journal of Agricultural Research, 2015)
Fusarium oxysporum (Fo), F. proliferatum (Fp) and F. solani (Fs) are causal agents associated with roots of asparagus affected by crown and root rot, a disease inflicting serious losses worldwide. The propagule viability of Fusarium spp. was determined on substrate artificially infested with Fo5, Fp3 or Fs2 isolates, amended with either poultry manure (PM), its pellet (PPM), or olive residue compost (ORC) and, thereafter, incubated at 30 or 35°C for different periods. Inoculum viability was significantly affected by these organic amendments (OAs) in combination with temperature and incubation period. The greatest reduction in viability of Fo5 and Fs2 occurred with PPM and loss of viability achieved was higher at 35°C than at 30ºC, and longer incubation period (45 days). However, the viability of Fp3 did not decrease greatly in most of the treatments, as compared to the infested and un-amended control, when incubated at 30ºC. After incubation, seedlings of asparagus `Grande´ were transplanted into pots containing substrates infested with the different species of Fusarium. After three months in greenhouse, symptoms severity in roots showed highly significant decreases, but Fp3 caused lower severity than Fo5 and Fs2. Severity reduction was particularly high at 30ºC (by 15 days incubation for Fs2 and by 30-45 days for Fo5), after PPM treatment, as well as PM-2% for Fo5 and Fs2 incubated during 30 and 45 days at both temperatures, and with ORC (15-30 days incubation). Moreover, assessment of plants fresh weight showed significantly high increases in Fo5 and Fs2, with some rates of the three OAs tested, depending on incubation period and temperature.